The Mechanosensitive Ion Channel MSL10 Modulates Susceptibility to Pseudomonas syringae in Arabidopsis thaliana - Debarati Basu; Jennette M. Codjoe; Kira M. Veley; Elizabeth S. Haswell (Molecular Plant-Microbe Interactions, 2022)
Plants sense and respond to molecular signals associated with the presence of pathogens and their virulence factors. Mechanical signals generated during pathogenic invasion may also be important, but their contributions have rarely been studied. Here, we investigate the potential role of a mechanosensitive ion channel, MscS-like (MSL)10, in defense against the bacterial pathogen Pseudomonas syringae in Arabidopsis thaliana. We previously showed that overexpression of MSL10-GFP, phospho-mimetic versions of MSL10, and the gain-of-function allele msl10-3G all produce dwarfing, spontaneous cell death, and the hyperaccumulation of reactive oxygen species. These phenotypes are shared by many autoimmune mutants and are frequently suppressed by growth at high temperature in those lines. We found that the same was true for all three MSL10 hypermorphs. In addition, we show that the SGT1/RAR1/HSP90 cochaperone complex was required for dwarfing and ectopic cell death, PAD4 and SID2 were partially required, and the immune regulators EDS1 and NDR1 were dispensable. All MSL10 hypermorphs exhibited reduced susceptibility to infection by P. syringae strain Pto DC3000 and Pto DC3000 expressing the avirulence genes avrRpt2 or avrRpm1 but not Pto DC3000 hrpL and showed an accelerated induction of PR1 expression compared with wild-type plants. Null msl10-1 mutants were delayed in PR1 induction and displayed modest susceptibility to infection by coronatine-deficient P. syringae pv. tomato. Finally, stomatal closure was reduced in msl10-1 loss-of-function mutants in response to P. syringae pv. tomato COR−. These data show that MSL10 modulates pathogen responses and begin to address the possibility that mechanical signals are exploited by the plant for pathogen perception.[Graphic: see text] Copyright © 2022 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.